(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
The paper lists the works of Aníbal Quijano and Judith Butler, as keys to thinking about some onto-epistemological challenges put to Science Education. We selected for analysis the concepts of “Coloniality” (Quijano) and “Schemas of Intelligibility” and “Precariousness” (Butler), instigated by some questions: How are these concepts articulated? Is it possible to find points of convergence between both so that we can think about promoting the right to be and to know in Science Education? The text incorporates a bibliographic research, starting from two moments: a) theoretical-methodological analysis of the approaches of the authors mentioned; b) a discussion on the way they articulate themselves from the analysis of three books that deal with decoloniality in Science Education. The material is interpreted from the discussions held in the Social Sciences and Science Education and which aim to think about the conditions for the production of scientific knowledge.